Lanthanide metal-organic frameworks (UPMOFs) as emerging adsorbents for rapid removal of crystal violet - Mohamed Tahir, Mohamed Ibrahim; Shahrin, Irdina; Dusti, Nur Ainina; Rayung, Marwah; Muhammad Nasri, Nazhirah (Elsevier B.V., 2025)
Lanthanum- and neodymium-based metal-organic frameworks (UPMOF710 and UPMOF713) were investigated for their potential in the removal of crystal violet (CV) from aqueous solution. These frameworks are constructed using two different carboxylate linkers; 1,4-benzenedicarboxylic acid (BDC) and 4,4-oxybisbenzoic acid (OBA). Both UPMOF710 and UPMOF713 exhibited rapid uptake of CV, attaining adsorption equilibrium within 20 min. The adsorption performance was largely unaffected by variation of pH in the range of 3–10, demonstrating the stability and pH tolerance of the frameworks under acidic to alkaline conditions. The removal efficiency of CV removal was significantly improved with increasing adsorbent dosage from 5 to 25 mg. The best fitted kinetic data for this study was described by the pseudo-second-order model, indicating the chemisorption process, as supported by the good agreement between the experimental adsorption capacities (19.10 mg/g for UPMOF710 and 18.86 mg/g for UPMOF713), together with higher correlation coefficients. UPMOF710 adsorption behaviour fitted with the Freundlich isotherm, suggesting multilayer adsorption on heterogeneous surface sites, whereas UPMOF713 followed the Langmuir isotherm model revealing monolayer adsorption on homogenous sites. The findings highlight the applicability of these rare-earth MOFs for dye removal and expanding their functional scope beyond structural studies. Both frameworks also demonstrated their potential in water remediation.